Educational poetry in the Mamluki and Ottoman eras: factors of prosperity and decline - Al Bursaidi, Salem bin Saeed bin Nasser (Arab Journal for Sciences and Research Publishing, 2016)
This research deals with educational poetry in the Mamluk and Ottoman periods, focusing on the reasons for its prosperity, and then the factors of decline in its presence thereafter, and began the research with a brief introduction to educational poetry and the stages of its development in Arabic literature up to the Mamluk and Ottoman periods, and then addressed the reasons for the prosperity Educational poetry in the Mamluk and Ottoman periods, and then the researcher addressed models of educational poetry in this period (in readings, jurisprudence, grammar, rhetoric, animals and mathematics), after which the research touched on the characteristics of the general educational poetry in this era in terms of its reliance on the disaffected brevity, And attention to verbal explanations, which led to serious results at the scientific level, addressed by the research in some detail, and these results had the effect of declining the presence of educational poetry in our reality today, to discuss the prospects of the future of educational poetry and the conditions of repair of the defect, and the areas in which it can be attended Educational poetry again.
Keywords: didactic poetry; Mamluk and Ottoman eras; factors of prosperity and decline; Mamluk; Ottoman